Analisis Kompetensi Pedagogik dan Kompetensi Profesional Guru di Sekolah Dasard - Halimah, Lilis Mulyatul (Universitas Negeri Malang, 2023)
Abstract: This research is motivated by the importance of teacher pedagogic and professional competence in elementary schools to improve the quality and quality of education in these institutions. The competence of teachers in elementary schools is the most important factor for influencing students in the class in the learning process in order to increase students' grades. This study aims to explain the analysis of teacher competence, namely the pedagogic competence and professional competence of teachers in elementary schools. The approach in this research is descriptive qualitative. For respondents in this study, namely elementary school teachers from grade 1 to grade 6 totaling 6 people with pre-field research stages, field observations, interviews, documentation, and carrying out data analysis and drawing conclusions generated by researchers. In increasing the realization of teacher competence in elementary schools it is very necessary to realize the education that has been aspired so far. Teacher pedagogic competence can be developed through optimizing teacher performance, such as administrative completeness in teaching and readiness of learning media in class and others to support an interesting and fun learning process for students in class. Whereas optimizing the professional competence of teachers in elementary schools can be done by attending seminars, in-house training (IHT) and teacher working group activities or KKG to improve self-quality periodically and continue to upgrade themselves even better with increasingly developing mastery of technology skills.Keywords: Teacher, Teacher Competence, Pedagogic, Professional, Elementary SchoolAbstrak: Penelitian ini dilatarbelakangi pentingnya akan kompetensi pedagogik dan profesional guru di sekolah dasar untuk meningkatkan mutu dan kualitas pendidikan yang ada di instansi tersebut. Kompetensi guru di sekolah dasar merupakan faktor yang paling utama untuk mempengaruhi peserta didik di kelas dalam proses pemnbelajaran agar meningkatkan perolehan nilai peserta didik. Dalam penelitian ini bertujuan untuk menjelaskan mengenai analisis kompetensi guru yaitu kompetensi pedagogik dan kompetensi profesional guru di sekolah dasar. Pendekatan dalam penelitian ini yaitu kualitatif deskriptif. Untuk responden dalam penelitian ini yaitu guru sekolah dasar dari mulai kelas 1 sampai kelas 6 berjumlah 6 orang dengan tahapan penelitian pra-lapangan, observasi ke lapangan, wawancara, dokumentasi, dan melaksanakan analisis data serta menarik kesimpulan yang dihasilkan oleh peneliti. Dalam meningkatkan realisasi kompetensi guru di sekolah dasar sangat diperlukan untuk terjalinnya pendidikan yang di cita-citakan selama ini. Kompetensi pedagogik guru bisa dikembangkan melalui pengoptimalan kinerja guru tersebut, seperti kelengkapan administrasi dalam mengajar dan kesiapan media pembelajaran di kelas dan lainnya untuk menunjang proses pembelajaran yang menarik dan menyenangkan untuk peserta didik di kelas. Sedangkan untuk pengoptimalan kompetensi profesional guru di sekolah dasar dapat dilakukan dengan mengikuti seminar-seminar, in house training (IHT) dan kegiatan kelompok kerja guru atau KKG untuk meningkatkan kualitas diri secara periodik dan terus meng-upgrade diri lebih baik lagi dengan keterampilan penguasaan ilmu teknologi yang semakin berkembang.Kata kunci: Guru, Kompetensi Guru, Pedagogik, Profesional, Sekolah Dasar